Neighborhoods, criminal Incidents, race, and sentencing: exploring the racial and social context of disparities in incarceration sentences - Donnelly, Ellen A. (The British journal of criminology, 2022)
As an extra-legal factor, social context is a key contributor to racial/ethnic disparities in incarceration sentences. Neighborhoods may have important, yet underexplored influences on sentencing. This study evaluates whether the social conditions and racial characteristics of communities where defendants allegedly offend affect Black-White sentencing disparities. Three-level multilevel model results suggest larger Black populations in neighborhoods of criminal incident increase the odds of incarceration and, to a lesser extent, lengthen sentences for all defendants. Offending outside one’s residential community increases the probability and length of a prison sentence. Neighbourhood effects differ by race, however. Unlike Whites, Blacks receive more punitive sentences for committing offences in disadvantaged areas and less proportionally Black communities. Neighbourhoods thus contribute to racial differences in sentencing outcomes.